Date with the Unknown - Salem, Atef; Al-Faisi; Isa, Masud; Sharif, Omar; Gamal, Samia; Glowalla, Samia
Classic Egyptian film noir starring the brilliant Omar Sharif who is trying to find out the mysterious circumstances under which his brother was killed. This gem also features the fabulous belly dancer Samia Gamal and features some of her famous exotic dancing tableaux. [Cover]